Analisis Lingkungan Belajar Sekolah Terhadap Motivasi Siswa Kelas I SDN 2 Babakanrema - Rohendi, Endi; Sutarna, Nana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the role of the school environment in increasing students' motivation for independent learning in the lower grades of SDN 2 Babakanrema. Teachers and homeroom teachers are considered to have an important role as role models in helping students develop independence, given that school is a “second home” for students. This study uses a case study method with a qualitative approach. The research subjects are lower grade students at SDN 2 Babakanrema. Data were collected through observation, interviews, and documentation, then analyzed using qualitative descriptive techniques. The results of the study indicate that school environmental facilities play a positive role in increasing student motivation for independence. Discussions with homeroom teachers reveal that there is an annual increase in student independence, both among existing and new students. In addition, observations show that a clean and well-organized physical school environment creates a comfortable learning environment, thereby contributing to an increase in student motivation for independence. These findings emphasize the importance of consistency in maintaining and improving the quality of the learning environment.